Activins and prolactinoma development II: effects of an ovariectomy - Faraoni, Erika Yanil (2018)
It was previously shown that an ovariectomy (OVX) prevents pituitaryhyperplasia in Drd2-/- and hCGβ+ female mice, indicating theparticipation of ovarian factors in the development of prolactinoma.However, a hormone replacement with estradiol after OVX does notrestore tumor development.